Improving high school student learning outcomes: Using problem-based learning model - Sartika, Sri Hardianti; Puspitasari, Erna; Suherti, Heti (Educenter : Jurnal Ilmiah Pendidikan, 2024)
Student learning outcomes are an indicator of the success of teaching and learning activities carried out. This research aims to determine the improvement in student learning outcomes in economics courses by implementing the problem-based learning model a quantitative research method with a quasi-experimental approach. The population of this research was 205 students in class XI social at SMAN 7 Tasikmalaya, and the sample used was 136 students using a purposive sampling technique consisting of two experimental classes and two control classes. The experimental class uses the Problem-Based Learning learning model, while the control class uses the conventional learning model. Students in each class are given a pretest, and then learning is carried out according to a predetermined model, and then a posttest is carried out. The questions used are 25 multiple-choice questions, and then the results or grades obtained by students are analyzed further.  The results of this study show that there are differences between before and after treatment in the experimental class and control class. This research concludes that the implications of implementing a problem-based learning model as an alternative to conventional models can be used in an effort to improve student learning outcomes in economics courses.